Hepatic arterial interventional therapies alone or in combination with molecular targeted therapies and PD-(L)1 inhibitors in locally aggressive, early recurrent hepatocellular carcinoma: a retrospective study - Luo, Weixin; Liu, Lixuan; Lin, Wenping; Mei, Jie; Lin, Yansong; Yang, Zhoutian; Liu, Fangyi; Wei, Wei; Guo, Rongping; Yun, Jingping (Frontiers in Immunology, 2025)
BackgroundCurrent treatment strategies for locally aggressive (beyond Milan criteria), early recurrent hepatocellular carcinoma (erHCC) lack consensus. This study aims to compare the efficacy of hepatic arterial interventional therapies (HAIT) combined with molecular targeted therapies and PD-(L)1 inhibitors (HAIT-M-P) versus HAIT alone for locally aggressive erHCC.MethodsThis study retrospectively reviewed the data of locally aggressive erHCC patients treated with HAIT alone or HAIT-M-P at Sun Yat-sen University Cancer Center from 2020 to 2024. The progression-free survival (PFS), overall survival (OS), tumor responses, and treatment-related adverse events (TRAEs) were compared. Propensity score matching (PSM) and multivariate Cox regression model were used to minimize confounding bias.ResultsA total of 101 patients with locally aggressive erHCC were enrolled. Compared with the HAIT group (n=51), the HAIT-M-P group (n=50) demonstrated significantly longer median PFS (10.1 months vs. 3.7 months, HR = 0.36, P < 0.001) and comparable median OS (not reached vs. 38.2 months, HR = 0.45, P = 0.065). After PSM, 24 pairs of patients were included. The HAIT-M-P group maintained a significant median PFS advantage (12.8 months vs. 3.7 months, HR = 0.28, P < 0.001) and comparable median OS (not reached vs. 38.2 months, HR = 0.56, P = 0.330). In the multivariate Cox regression analysis, the HAIT-M-P group demonstrated a significant improvement in OS (HR = 0.30, P = 0.033). The objective response rate and disease control rate were significantly higher in the HAIT-M-P group than in the HAIT group, respectively, according to the RECIST v1.1 (30.0% vs. 7.8%, P = 0.009; 82.0% vs. 54.9%, P = 0.007) and mRECIST criteria (56.0% vs. 19.6%, P < 0.001; 90.0% vs. 58.8%, P = 0.001). The grade 3 – 4 TRAEs between the two groups were comparable (19.6% vs. 34.0%, P = 0.159).ConclusionCompared with HAIT alone, HAIT-M-P was associated with improved PFS and tumor response rates, and showed a possible trend toward improved OS in patients with locally aggressive erHCC, which warrants further validation.